Effect of cavitation inducers on slurry erosion resistance of HVOF-sprayed stainless-steel coatings - M. S., Prathap; H. J., Amarendra; K. A., Venugopal; Avalappa, Manjunath G.; Deshpande, Uttam U. (Frontiers in Materials, 2025)
High-Velocity Oxy-Fuel (HVOF) spraying has extensively been used for improving erosion resistance of stainless-steel parts exposed in aggressive conditions. The paper addresses the behavior of wear loss for HVOF-sprayed stainless steel coatings during slurry erosion under conditions with and without a cavitation inducer condition. Slurry erosion experiments with 20-h wear testing at 5-h intervals with measurements were conducted by using silica sand (600 µm) with a 10 wt.% solution of tap water. The findings suggest that the availability of cavitation inducers has a considerable influence on wear resistance, with some of the samples developing an increase in wear loss at shorter times, and others showing lesser material loss over time. Notably, the 20Ni80Cr sample developed an increase in wear loss at 5 h, whereas other samples developed responses at later stages. The research emphasizes the mechanical impact’s role in changing erosion mechanisms and offers information on how to optimize HVOF coatings for enhanced durability in industrial use.